The price of pressure: nationwide survey on lifestyle disturbances, occupational burnout and compromised perceived-competency among radiology residents in China - Liu, Zeqi; Yao, Qinqi; Wang, Peicheng; Shen, Lijun; Li, Hange; Zhang, Jingfeng; Jiang, Maoqing; Yang, Zhenghan; Wang, Zhenchang; Zheng, Jianjun; Zhu, Jiming; Wu, You (Frontiers in Public Health, 2024)
Objectives: The competency of radiology directly affects the quality and equity of medical services. Due to their different occupational characteristics compared to other specialists, this study aims to evaluate the impacts of lifestyles on competency and burnout in radiology residents in China. Materials & Methods: A nationwide, cross-sectional survey was conducted from December 1, 2020 to April 30, 2021. 12,208 radiology residents during their standardized residency training in China were invited. Multivariate linear regression and logistic regression were conducted to identify perceived competency and burnout associated with lifestyles. Results: Of the 3,666 participants, 58.02% were female, 82.24% were aged < 30 years, 40.53% were from the Eastern region, and 92.06% obtained a bachelor’s degree. The radiology residents with high-level lifestyles had higher competency (β = 0.16, 95% CI: 0.01, 0.32), particularly in the realms of sleep, physical activity, and alcohol consumption. The correlation was stronger in residents with longer work hours and more night shifts. Residents with insomnia (OR = 7.69, 95% CI = [4.23, 14.67]) and less exercise (OR = 6.24, 95% CI = [1.33, 29.37]) had higher burnout risk, while residents who smoked had a lower risk (OR = 0.60, 95% CI = [0.40, 0.89]). And lifestyle factors had a slightly different impact on emotional exhaustion and depersonalization. Conclusions: Radiology residents’ lifestyles can be emphasized, as it may reflect their pressure and well-being and influence their concentration, competency, burnout and performance. Policymakers and hospital administrators should incorporate practical and modifiable strategies into work routines to improve the lifestyle quality of residents.